2021
DOI: 10.3390/agriculture11020111
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of Soil Organic Matter in Satisfying the Phosphorus Requirements of Olive Trees (Olea europaea L.)

Abstract: Under high organic matter content, even under low extractable soil P concentrations, sufficient or over-sufficient foliar P levels may be found. This multi-year study aimed at examining the effects of organic matter content and irrigation management on (a) soil fertility, (b) P-cycle related soil enzymes (acid and alkaline phosphatase, pyrophosphatase) and (c) foliar nutrient concentrations. Irrigated and non-irrigated groves of fully productive trees of the cultivar “Chondrolia Chalkidikis” with low organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, application of organic fertilizers can increase phoD gene and phoD‐harbouring bacteria in the soil, which promoted the solubility of inorganic P (Bi et al., 2019; Hu et al., 2018). At the same time, organic matter addition enhances soil phosphatase activity, which converts organic P into inorganic phosphorus (Christopoulou et al., 2021). We found that the application of organic fertilizer increased the Olsen‐P content increased by 82% compared with soils without fertilizers, which could promote crop growth and development.…”
Section: Resultsmentioning
confidence: 99%
“…For example, application of organic fertilizers can increase phoD gene and phoD‐harbouring bacteria in the soil, which promoted the solubility of inorganic P (Bi et al., 2019; Hu et al., 2018). At the same time, organic matter addition enhances soil phosphatase activity, which converts organic P into inorganic phosphorus (Christopoulou et al., 2021). We found that the application of organic fertilizer increased the Olsen‐P content increased by 82% compared with soils without fertilizers, which could promote crop growth and development.…”
Section: Resultsmentioning
confidence: 99%
“…Clear P‐deficiency symptoms in olives are rare 44,45 and P used to be applied only on the basis of leaf analyses, with 0.1% as a threshold value below which deficiency was considered 1,34,46 . Furthermore, some studies claimed that olives do not require P fertilization at all, especially if they are grown in soils that are rich in organic matter 47 . This was based on the presence of large amounts of total P in most soils on the one hand, and the extensive root system of olives coupled with mycorrhizal symbiosis on the other 48 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 34 , 46 Furthermore, some studies claimed that olives do not require P fertilization at all, especially if they are grown in soils that are rich in organic matter. 47 This was based on the presence of large amounts of total P in most soils on the one hand, and the extensive root system of olives coupled with mycorrhizal symbiosis on the other. 48 Consequently, the number of studies dealing with the effect of P fertilization on olive oil quality and composition is limited.…”
Section: Discussionmentioning
confidence: 99%